1994
DOI: 10.2307/3495877
|View full text |Cite
|
Sign up to set email alerts
|

Resistance of Selected Interspecific Lycopersicon Hybrids to Greenhouse Whitefly (Homoptera: Aleurodidae)

Abstract: JSTOR is a not-for-profit service that helps scholars, researchers, and students discover, use, and build upon a wide range of content in a trusted digital archive. We use information technology and tools to increase productivity and facilitate new forms of scholarship. For more information about JSTOR, please contact support@jstor.org.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2005
2005
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 3 publications
0
12
0
Order By: Relevance
“…Test statistic, U (df = 34) = 28.5 presence of very dense hairs on the leaf surfaces, physically preventing the whitefly from effectively probing. Erb et al (1994) attributed the greater resistance of L. pennellii to T. vaporariorum to toxic exudates from glandular trichomes. Firdaus et al (2012) also suggest that the resistance found in L. pimpinellifolium is based upon the presence of type IV trichomes.…”
Section: Whitefly Movement Trialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Test statistic, U (df = 34) = 28.5 presence of very dense hairs on the leaf surfaces, physically preventing the whitefly from effectively probing. Erb et al (1994) attributed the greater resistance of L. pennellii to T. vaporariorum to toxic exudates from glandular trichomes. Firdaus et al (2012) also suggest that the resistance found in L. pimpinellifolium is based upon the presence of type IV trichomes.…”
Section: Whitefly Movement Trialsmentioning
confidence: 99%
“…glabratum used in the study (those tested at 14 weeks rather than 8) displayed enhanced resistance, which has interesting implications for the present study in that the apparent resistance observed in L. pimpinellifolium in the present work at the 3-4 leaf stage (∼3 weeks old) may increase as the plants age. Erb et al (1994) studied the potential of another wild tomato species, Lycopersicon pennellii, to act as a source of resistance traits against T. vaporariorum. Hybrids produced using this species supported the fewest eggs and were the least attractive hosts of the whitefly.…”
Section: No Choice Assays To Record Whitefly Ovipositionmentioning
confidence: 99%
“…The life history traits and/or population growth of T. vaporariorum have been studied on tomato (Solanum lycopersicum) in order to investigate the resistance of various tomato cultivars, breeding lines and hybrids to this pest (Romanow et al, 1991;Bas et al, 1992;Erb et al, 1994;Lucatti et al, 2010). In spite of the economic importance of T. vaporariorum, we found no published data on the life history of this pest on the most widely grown tomato genotypes in Serbian greenhouses.…”
Section: Resultsmentioning
confidence: 70%
“…Erb et al (1994) found a reduced number of laid eggs and F2 adults on two interspecific hybrids between S. lycopersicum and wild tomato species. In a five-day no-choice bioassay, Lucatti et al (2010) found the oviposition rate of T. vaporariorum to range from 0.2 eggs/day on a wild line S. habrochaites to 4.4 eggs/day on a S. lycopersicum breeding line resistant to root knot nematodes.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation